Two new species of Micropsalliota (Agaricaceae/Agaricales) from Thailand - He, Maoqiang; Hyde, Kevin D.; Cheewangkoon, Ratchadawan; Zhao, Ruilin (Phytotaxa, 2020)
Micropsalliota embraces approximately 70 species which are mainly distributed in tropical and subtropical areas. In this study, two new species named Micropsalliota albella and M. purpureobrunneola are introduced from northern Thailand. Phylogenetic analyses based on ITS and LSU data shows their placement in Micropsalliota in two distinct lineages. Micropsalliota albella is characterized by the white, tiny basidiomes and utriform cheilocystidia. Micropsalliota purpureobrunneola is characterized by the pileus finely covered with purple to brownish-purple scales, oblong basidiospores and narrowly clavate cheilocystidia. Descriptions, colour photographs and illustrations of both new species are presented.